Des phoques et des âmes, évolution de la place des phoques dans la vision du monde des pêcheurs artisans pêcheurs islandais - Niels Einarsson (VertigO)
This article is a translation of Of seals and souls: Changes in the position of seals in the world-view of Icelandic small-scale fishermen, published in 1990 in volume 3, number 2 of Maritime Anthropological Studies. It was translated by Karina Gerdau. This article deals with the changing attitudes of Icelandic artisanal fishermen towards seals. The material on which this study is based comes from fieldwork in a fishing village on Iceland's east coast, but also from the author's experience as a native participant in artisanal fishing. It is often argued that, in order to understand a particular cultural change, it is necessary to see how it is "externally induced yet indigenously orchestrated" (Sahlins, 1985. p. viii). In this case, the external influence came from campaigns against the slaughter of marine mammals by environmental and animal protection organizations.